Controllable synthesis of few-layered and hierarchically porous boron nitride nanosheets. Issue 20 (12th February 2016) - Xiao, Feng; Chen, Zhixin; Casillas, Gilberto; Richardson, Christopher; Li, Huijun; Huang, Zhenguo
Abstract : Few-layered porous boron nitride nanosheets prepared using MgB2 as a dynamic template show good CO2 adsorption selectivity. Abstract : Few-layered porous boron nitride nanosheets (BNNS) have been prepared using a dynamic magnesium diboride (MgB2 ) template and ammonium chloride (NH4 Cl) etchant. Magnesium-based intermediates serve as layer separators in the synthesis and prevent extensive aggregation, resulting in few-layered BNNS. The resultant BNNS are hierarchically porous and show good CO2 /N2 adsorption selectivity.